P2X7 receptor induces microglia polarization to the M1 phenotype in cancer-induced bone pain rat models. (20th January 2022) - Wu, Ping; Zhou, Guohua; Wu, Xiaoqi; Lv, Run; Yao, Jiaqi; Wen, Qingping
Background: The transition from pro-inflammatory M1 phenotype to anti-inflammatory M2 phenotype presents a novel therapeutic strategy for chronic pain. Objective: We investigated the role of microglia polarization in cancer-induced bone pain (CIBP), as well as the role of the P2X7 receptor in modulating M1 to M2 polarization. Methods: Walker-256 breast cancer cells were administered into tibias of female rats to induce bone cancer–associated cancer. Results: During bone cancer development, the P2X7 receptor and M1 microglia markers were upregulated. In contrast, inhibition of the P2X7 receptor by BBG, a blood-brain barrier-permeable P2X7R-specific antagonist, alleviated the pain and promoted microglia polarization toward the M2 phenotype, while suppressing the M1 phenotype in vivo and in vitro . Conclusion: P2X7 receptor-mediated spinal microglia polarization is involved in alleviation of CIBP. Therefore, P2X7R is a potential option for CIBP treatment.